Determinants of abortion among clients coming for abortion service at felegehiwot referral hospital, northwest Ethiopia: a case control study. Issue 1 (December 2017) - Tilahun, Fikreselassie; Dadi, Abel; Shiferaw, Getachew
Abstract Background According to the World Health Organization (WHO) estimate, one-third of pregnancies end in miscarriage, stillbirth, or induced abortion in the world. There are various reasons for a woman to seek induced abortion. However, limited information is available so far in the country and particularly in the study area. Therefore, the aim of the current study was to identify the determinants of induced abortion among clients coming for abortion care services at Bahirdar Felegehiwote referral hospital, Northwest Ethiopia. Methods Institutional based unmatched case-control study was conducted from September to December 2014. Interview administered questioner was used to collect primary data. Enumeration and systematic random sampling (K = 3) method was used to select 175 cases and 350 controls. A binary logistic regression model was fitted to identify determinant factors. Odds ratio with 95% CI was computed to assess the strength and significance of the association. Result All sampled cases and controls were actually interviewed. The likelihood of abortion was higher among non-married women [AOR: 18.23, 95% CI: 8.04, 41.32], students [AOR: 11.46, 95% CI: 6.29, 20.87], and women having a monthly income of less than 500 ETB [AOR: 11.46, 95% CI: 6.29, 20.87]. However, the likelihood of abortion was lower among women age greater than 24 years [AOR: 0.29, 95% CI: 0.11, 0.79] and who had the previous history of induced abortion [AOR: 0.31, 95% CI: 0.15, 0.65]. Conclusion The study identified being non-married, student, women age less than 24 years, having the previous history of induced abortion, and low monthly income as an independent determinant of induced abortion. Interventions focused on the identified determinant factors are recommended.